Maternal Thyroid Disorders and Risk of Autism Spectrum Disorder in Progeny. Issue 3 (May 2020) - Rotem, Ran S.; Chodick, Gabriel; Shalev, Varda; Davidovitch, Michael; Koren, Gideon; Hauser, Russ; Coull, Brent A.; Seely, Ellen W.; Nguyen, Vy T.; Weisskopf, Marc G.
Abstract : Background: Maternal thyroid dysfunction is suspected of causing adverse neurodevelopmental effects, but current evidence is inconclusive. Epidemiologic investigations generally suggest an association between maternal thyroid dysfunction and neurodevelopment impairments in progeny, but clinical trials of thyroid treatment during pregnancy reported null effects. To better understand these discrepant findings, we evaluated the association between maternal thyroid conditions and autism spectrum disorder (ASD), including examining the role of gestational thyroid-related hormone concentrations and thyroid medications use. Methods: Analyses considered 437, 222 singleton live births occurring in a large Israeli health fund in 1999–2013, followed through 2016. Thyroid conditions and ASD cases were identified through International Classification of Diseases-9 codes with subsequent validation through review of medical records. Laboratory gestational thyroid hormone measurements were also considered. Results: Children of mothers who ever experienced hypothyroidism had a higher risk of ASD compared with children of mothers without hypothyroidism (adjusted odds ratio [aOR] = 1.26, 95% confidence interval [CI] = 1.12, 1.42). The association with hyperthyroidism was less consistent, but elevated in main analyses (aOR = 1.42, 95% CI = 1.04, 1.94). These associations were not explained by maternal gestational thyroid hormones levels nor mitigated by gestational use of thyroid medications. Conclusions: Results indicate that maternal thyroid conditions are associated with increased ASD risk in progeny, but suggestively not due to direct effects of thyroid hormones. Instead, factors that influence maternal thyroid function could have etiologic roles in ASD through pathways independent of maternal gestational thyroid hormones and thus be unaffected by medication treatment. Factors known to disrupt thyroid function should be examined for possible involvement in ASD etiology. Abstract : Supplemental Digital Content is available in the text.